Correction: Bakuchiol – a natural meroterpenoid: structure, isolation, synthesis and functionalization approaches. Issue 17 (7th April 2022) - Krishna, T. P. Adarsh; Edachery, Baldev; Athalathil, Sunil
Abstract : Correction for 'Bakuchiol – a natural meroterpenoid: structure, isolation, synthesis and functionalization approaches' by T. P. Adarsh Krishna et al., RSC Adv., 2022, 12, 8815–8832, DOI: ; 10.1039/D1RA08771A .